Ujub Bersih Dhusun Gobed Kasembon Kabupaten Malang dalam Perspektif Semiotika Roland Barthes - Sungging Widagdo; Dandung Adityo Argo Prasetyo; Dimas Tegar Vebriano (Universitas Veteran Bangun Nusantara, 2026)
The Bersih Dhusun Gobed tradition is often perceived by some members of the community as a form of shirk due to the presence of ujub, which is assumed to contain mystical elements. This perception arises from a limited understanding, as people generally only hear the recitation of ujub without fully comprehending its linguistic structure, content, and deeper meaning. Therefore, this study aims to analyze the words, phrases, sentences, and discourse of ujub in the Bersih Dhusun Gobed tradition in order to reveal its meaning and function within the ritual context. This research employs a descriptive qualitative method with an objective approach, focusing on the textual analysis of ujub as a form of oral literature. The findings show that ujub represents an oral literary form of Javanese poetry characterized by poetic elements such as purwakanthi guru swara, purwakanthi guru sastra, and the use of syntactic repetition. In addition, ujub contains prayers and supplications addressed to Gusti Allah, symbolically conveyed through offerings and expressions of respect toward ancestors. Thus, the ujub mantra can be understood as a form of modern Javanese poetic expression that functions as a medium of prayer and cultural articulation.